Altri orientalismi L'India a Firenze 1860-1900 - Vicente, Filipa Lowndes (Studi e saggi, 2012)
Other Orientalisms analyses various forms of knowledge about India through the circulation of people, ideas, knowledge, images and objects between Florence and Bombay. In the second half of the nineteenth century Florence became an important centre for studies on India, manifested in the organisation of exhibitions, museums, journals and international conferences. Inspired by the relationship between two Indianists - the Italian Angelo De Gubernatis, a teacher of Sanskrit in Florence and the Goan José Gerson da Cunha, a physician and historian in Bombay - this book discloses an India that emerged from different places, peopled by a multiplicity of voices. The institutional, intellectual and museum experience of Florentine orientalism, albeit peripheral, further enhances the debate on knowledge and colonial power that has engaged social and human sciences in recent decades.